Diagnóstico del derecho a la educación inicial intercultural en la comunidad de Palmira, cantón San Miguel de Urcuquí de la provincia de Imbabura en el período 2023-2024 - Coral Morillo, Yomaira Fernanda (2025)
The main objective of this research work was to carry out a diagnosis of the right to early education in the community of Palmira, canton of San Miguel de Urcuquí, province of Imbabura in the period 2023-2024, by identifying and analyzing the conditions and factors that affect its exercise, in order to propose recommendations aimed at renewing access and quality of early education in the community. To carry out this study, doctrinal and legal sources were analyzed, effectively supporting the existing problem. The research design is documentary, with a qualitative and quantitative approach, with an exploratory level of depth, through analytical, normative and socio-legal methods, with the use of documentary analysis techniques, as well as with the help of the interview and the survey. As a result, since 2021, access to intercultural early childhood education has been guaranteed in the community of Palmira in the canton of San Miguel de Urcuquí in the province of Imbabura, since, due to the efforts made by the authorities and the community members, it has been implemented in the Educational Unit 'San Francisco de Palmira', due to the efforts made by the authorities and the inhabitants, they managed to enable intercultural early childhood education for children aged 3 and 4, so that they can attend this preparation to strengthen their development of cognitive processes of inter-learning and multi-learning, reinforcing values, participation, democracy, among others. Concluding that within the framework of the doctrine and in Ecuadorian legislation, access to the right to early childhood intercultural education in indigenous communities is described, taking into account that Ecuador is a plurinational and intercultural State, which guarantees that children and adolescents can access educational establishments from the initial level to the higher level.